Method for evaluating shear resistance of shear nail of steel-LUHPC composite structure
By establishing the shear bearing capacity calculation formula and load-slip curve of shear nails in the steel-LUHPC combined structure, the problem that the existing specifications cannot calculate the shear resistance performance of shear nails is solved, and the shearing of the steel-LUHPC combined structure is realized The accurate evaluation of force nail performance provides technical support for the application of LUHPC materials in steel-mixed combined beam bridges.
Patent Information
- Application Number
- CN202411292311.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-07
AI Technical Summary
The existing specifications cannot effectively calculate the shear resistance of shear nails in steel-LUHPC combined structures, and it is difficult to meet the application needs of lightweight ultra-high performance concrete in steel-mixed combination beam bridges.
A method for evaluating shear performance of shear nails in steel-LUHPC combined structure is proposed. By establishing a calculation formula for shear bearing capacity and a load-slip curve, considering the different diameters and lengths of shear nails, and combining the test data to perform linear and non-linear Linear fitting, parameters a, b, and c are determined, and correlation coefficient R is derived to obtain the accurate shear bearing capacity and load-slip relationship.
The shear bearing capacity and load-slip change relationship of shear nails in steel-LUHPC combined structure can be accurately calculated, providing theoretical basis and technical support, and providing support for the application of LUHPC materials in steel-mixed combined beam bridges.
Smart Images

Figure CN119274706A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel-LUHPC composite structures, and in particular to a method for evaluating the shear performance of shear nails of a steel-LUHPC composite structure. Background Art
[0002] Steel-concrete composite beam bridges can give full play to the compressive strength of concrete and the tensile strength of steel, save engineering costs, and have broad application prospects in bridge engineering. However, with the increase in traffic volume and span requirements, traditional steel-concrete composite beam bridges are difficult to meet the requirements of social development. For example, the ordinary high-performance concrete currently used has high density and low strength, and the size and weight of prefabricated components are large, which limits the development of prefabrication assembly technology.
[0003] Lightweight Ultra-High Performance Concrete (LUHPC) has higher strength and smaller deadweight than ordinary concrete. The application of LUHPC materials to steel-concrete composite structures aims to improve the performance of concrete materials while reducing the deadweight of concrete, and further improve the mechanical performance of steel-concrete composite beam bridges. Steel-concrete composite beam bridges are connected to the concrete bridge deck and the steel main beam as a whole by setting shear nails, so that the composite beams can bear the force together. The current specifications for the calculation method of the bearing capacity of shear nails and the characteristics of the load-slip curve are mainly based on the shear test of ordinary high-performance concrete and shear nails, which is not suitable for the calculation of the shear bearing capacity of shear nails in steel-LUHPC composite structures. Therefore, in order to promote the application of LUHPC in steel-concrete composite beam bridges, it is very necessary to study the shear performance and calculation method of shear nail connectors under LUHPC conditions. Summary of the invention
[0004] The object of the present invention is to provide a method for evaluating the shear performance of shear studs of a steel-LUHPC composite structure, and to accurately determine the shear bearing capacity and load-slip curve calculation formula of the shear studs under LUHPC conditions.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is:
[0006] A method for evaluating the shear performance of shear studs of a steel-LUHPC composite structure comprises the following steps:
[0007] 1) Establish the calculation formula of shear bearing capacity of shear studs in steel-LUHPC composite structure:
[0008]
[0009] In the formula, A std is the cross-sectional area of the shear stud; f cu 、fstd is the compressive strength of the concrete cube and the tensile strength of the shear nail; E c 、E s is the elastic modulus of concrete and shear studs; a, b, c are all constants;
[0010] 2) The load-slip curve of shear studs in steel-LUHPC composite structures is proposed:
[0011]
[0012] Where, P is the shear force value of a single shear nail; P u is the shear bearing capacity of a single shear stud; s is the relative slip amount.
[0013] The method of the present invention solves the problem that the existing specifications do not consider the calculation of the shear performance of shear studs under LUHPC conditions, and provides technical support for the design and construction of steel-LUHPC composite structures.
[0014] Furthermore, a linear regression fitting was performed on the three parameters a, b, and c in step 1), and a=0.003, b=0.33, and c=0.17 were obtained;
[0015] The calculation formula for the shear bearing capacity of the shear studs in the steel-LUHPC composite structure is:
[0016]
[0017] Furthermore, by combining the push-out test data and formula (3), nonlinear fitting is performed on all push-out test results to obtain x=1.96, y=1.57. At this time, the correlation coefficient R=0.951;
[0018] Then the load-slip curve of the shear studs in the steel-LUHPC composite structure is:
[0019]
[0020] Compared with the prior art, the present invention has the following main advantages:
[0021] 1. The shear bearing capacity of shear studs in steel-LUHPC composite structures can be calculated by considering different diameters and lengths of shear studs.
[0022] 2. According to the relative slip between steel and concrete slab, the load-slip variation relationship of shear studs in steel-LUHPC composite structure is accurately determined.
[0023] 3. The present invention provides a theoretical basis and technical support for the application of LUHPC materials in steel-concrete composite beam bridges. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0025] Figure 1 It is a flow chart for calculating the shear bearing capacity and load-slip curve of the shear nails of the steel-LUHPC composite structure of the present invention;
[0026] Figure 2 The test specimen component diagram is introduced for the shear studs of the steel-LUHPC composite structure of the present invention. Figure 2 middle:
[0027] (a) Front view of the specimen;
[0028] (b) Side view of the specimen;
[0029] (c) Top view of the specimen;
[0030] (d) Shear stud detail drawing.
[0031] Figure 3 This is a schematic diagram of the test piece preparation process of the present invention. Figure 3 middle:
[0032] (a) Shear stud welding;
[0033] (b) tying steel bars;
[0034] (c) Mould assembly;
[0035] (d) Concrete pouring;
[0036] (e) Smoothing the surface;
[0037] (f) Specimen curing. DETAILED DESCRIPTION
[0038] The principles and features of the present invention are described below in conjunction with the accompanying drawings and specific embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0039] Example 1
[0040] A method for evaluating the shear performance of shear studs in steel-LUHPC composite structures, such as Figure 1 As shown, the following steps are included:
[0041] Step 1: Clarify the material properties of lightweight ultra-high performance concrete and the steel used, carry out shear nail push-out tests under LUHPC conditions, obtain the influencing factors and laws affecting the shear bearing capacity of shear nails, and combine the test data to establish the shear bearing capacity calculation formula of shear nails in steel-LUHPC composite structures;
[0042] Step 2: Study the relative slip value between steel and concrete slab under LUHPC conditions and propose the load-slip curve of shear studs in steel-LUHPC composite structures.
[0043] Furthermore, the present invention establishes a calculation formula for the shear bearing capacity of shear studs in a steel-LUHPC composite structure and proposes a load-slip curve of shear studs in a steel-LUHPC composite structure by means of an experimental method. The specific steps are as follows:
[0044] (1) According to the specification, 4 groups of 8 shear stud push-out specimens were designed and manufactured, with 2 identical specimens in each group, and the shear stud shear bearing capacity of different specimens was obtained, as shown in Table 4. Among them: Material parameters and manufacturing process are as follows:
[0045] According to the European Standard (Eurocode 4EN 1994-1-1:2004.Eurocode 4:Design of Composite Steel and Concrete Structures, Part 1-1:General Rules and Rules for Buildings[S].Brussels,Belgium:European Committee for Standardization,2004), the shear stud specimen construction dimensions are shown in Figure 2 As shown. The concrete is LUHPC, with a size of 650mm×600mm×150mm, cast in place, and equipped with HRB400 grade structural steel bars with a diameter of 8mm. The H-shaped steel beam is made of Q355B material, with a cross-sectional specification of HW300×300×20×20 and a length of 600mm. The shear nails are ML15AL, 4 on each side, with a vertical and horizontal spacing of 250mm×100mm.
[0046] In order to study the influence of shear stud diameter and length on the shear performance of shear studs in LUHPC, the shear stud diameter and length were selected as parameter variables, where the shear stud diameter was 13 mm / 16 mm, and the shear stud length was 80 mm / 120 mm. Two identical specimens were made in each group, with a total of 4 groups of 8 push-out specimens. The specimen parameters are shown in Table 1.
[0047] Table 1 Specimen parameters
[0048]
[0049] Note: LP in the number represents LUHPC, 80 / 120 represents the shear stud length, and 13 / 16 represents the shear stud diameter.
[0050] Mechanical properties tests were conducted on concrete, HRB400 steel bars and steel sections cured at room temperature in accordance with relevant specifications. Among them, the physical and mechanical properties of LUHPC materials were mainly tested for mechanical properties such as cube compressive strength, axial compressive strength and elastic modulus based on the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GB / T50081-2019) and the "Standard for Test Methods for Fiber Concrete" (CECS13-2009). Steel bars and steel sections were processed in accordance with the "Sampling Location and Sample Preparation for Mechanical Properties Test of Steel and Steel Products" (GB / T 2975-2018) specifications, and relevant material properties tests were conducted. The mechanical parameters of shear studs and steel fibers in LUHPC are the parameters provided by the manufacturer. The material parameters of each steel are shown in Table 2, and the mechanical properties of LUHPC are shown in Table 3.
[0051] Table 2 Steel material properties
[0052] Material Elastic modulus / GPa Yield strength / MPa Tensile strength / MPa Poisson's ratio Q355B 206 360 500 0.3 HRB400 200 400 570 0.3 13mm shear nail 206 340 460 0.3 16mm shear nail 206 340 460 0.3 Steel Fiber 210 — 2800 0.3
[0053] Table 3 LUHPC mechanical properties parameters
[0054] Material Cube compressive strength / MPa Axial compressive strength / MPa Elastic modulus / GPa LUHP 119.2 105 40.3
[0055] In the present invention, the LUHPC design parameters refer to: Cao Yugui, Ren Hanbing, Liu Muyu, et al. Research on the design parameter values of lightweight ultra-high performance concrete (LUHPC) [J]. Journal of Wuhan University of Technology, 2022, 44(12): 60-66; Among them, the steel fiber content in the LUHPC material is 2.0%.
[0056] When making the specimen, shear nails are welded at the corresponding positions on both sides of the steel plate. The steel cage uses HRB400 steel bars with a diameter of 8mm. The connection between the transverse stirrups and the longitudinal bars is mainly tied with steel wire. When pouring concrete, the specimen needs to be poured in layers. After pouring one layer, it is vibrated until it is dense before pouring the next layer. Bubbles are removed to increase strength. The specimen is demolded 2 days after pouring, and the specimen is covered with geotextile. The specimen is watered and cured for 28 days under natural conditions. The specific steps for making the specimen are as follows: Figure 3 shown.
[0057] Table 4 Shear bearing capacity of shear nail push-out specimens
[0058]
[0059] The experiment studies the influence of shear nail diameter and shear nail length on the shear bearing capacity of shear nails, and determines the calculation formula of shear bearing capacity of shear nails in steel-LUHPC composite structure:
[0060]
[0061] In the formula, Astd is the cross-sectional area of the shear stud; f cu 、f std is the compressive strength of the concrete cube and the tensile strength of the shear nail; E c 、E s is the elastic modulus of concrete and shear studs; a, b, c are all constants.
[0062] According to the test results in Table 4, regression fitting is performed on the three parameters a, b, and c, and the results are a=0.003; b=0.33; c=0.17.
[0063] The calculation formula for the shear bearing capacity of the shear studs in the steel-LUHPC composite structure is:
[0064]
[0065] Where: P u is the average shear bearing capacity of a single nail in Table 4; A std is the cross-sectional area of the shear stud; f cu 、f std is the compressive strength of the concrete cube and the tensile strength of the shear nail; E c 、E s is the elastic modulus of concrete and shear studs.
[0066] (2) The relative slip value between steel and concrete slab under LUHPC conditions was studied, and the load-slip curve calculation formula of shear studs in the steel-LUHPC composite structure was determined as follows:
[0067]
[0068] Where, P is the shear force value of a single shear nail; P u is the shear bearing capacity of a single shear stud; s is the relative slip amount.
[0069] Combining the test data in Table 4 with formula (3), nonlinear fitting is performed on all test results to obtain x=1.96, y=1.57. At this time, the correlation coefficient R=0.951.
[0070] Then the load-slip curve of the shear studs in the steel-LUHPC composite structure is:
[0071]
[0072] Example 2
[0073] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, specific application examples are provided below to further illustrate the present invention in detail.
[0074] There are 4 groups of 8 shear nail push-out specimens. The concrete is LUHPC, with a size of 650mm×600mm×150mm, cast in place, and equipped with HRB400 grade structural steel bars with a diameter of 8mm. H-shaped H-shaped steel is made of Q355B material, with a cross-sectional specification of HW300×300×20×20 and a length of 600mm. Shear nails are ML15AL, 4 are arranged on each side, and the longitudinal and transverse spacing is 250mm×100mm. According to formula (2), the calculated value and test value of the shear bearing capacity of the steel-LUHPC composite structure shear nail push-out specimen are shown in Table 5. It can be seen from Table 5 that the calculated value of the shear bearing capacity of the steel-LUHPC composite structure shear nail push-out specimen is in good agreement with the test value. The method for determining the shear bearing capacity of the steel-LUHPC composite structure shear nail of the present invention has an average value of the ratio of the theoretical calculated value to the test result of 0.99. It can be seen that the calculation formula for the shear bearing capacity of the steel-LUHPC composite structure shear nail of the present invention is highly accurate. The present invention can provide an experimental basis for promoting the application of LUHPC materials in steel-concrete composite beam bridges.
[0075] Table 5 Comparison between calculated and tested shear bearing capacity of shear nail push-out specimens of steel-LUHPC composite structure
[0076] Test piece number Test value / kN The formula of the present invention / kN Formula / test value of the present invention LP-80-13-1 100.3 84.9 0.85 LP-80-13-2 86.9 84.9 0.98 LP-80-16-1 123.3 128.7 1.04 LP-80-16-2 109.8 128.7 1.17 LP-120-13-1 99.7 84.9 0.85 LP-120-13-2 89.9 84.9 0.94 LP-120-16-1 111.1 128.7 1.16 LP-120-16-2 121.3 128.7 1.06 average value 0.99
[0077] The load-slip curve data calculated by formula (4) are compared with the test value results, as shown in Table 6. It can be seen that the load-slip curve relationship of the shear studs of the steel-LUHPC composite structure can be accurately calculated by adopting the present invention. The ratio of the two is about 1.06, which is consistent with the test value.
[0078] Table 6 Comparison of load-slip curves between calculated values and test values of the present invention
[0079] <![CDATA[Test value p / p u > <![CDATA[(Calculated value p / p u ) / (Test value p / p u ) <!-- 5 -->]]> 0.1 1.17 0.2 1.31 0.3 1.05 0.4 1.00 0.5 0.98 0.6 1.01 0.7 1.00 0.8 1.05 0.9 1.04 1 1.00 average value 1.06
[0080] In summary, the method of the present invention can accurately calculate the shear bearing capacity of the shear studs of the steel-LUHPC composite structure and clarify the load-slip relationship of the shear studs during the loading process. The present invention can provide an experimental basis for promoting the application of LUHPC materials in steel-concrete composite beam bridges.
[0081] The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Although the present invention has been described in detail with reference to the above embodiments, the present invention is not limited to the above specific implementation methods. Therefore, any modification or equivalent replacement of the present invention; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the invention are included in the scope of the claims of the present invention.
Claims
1. A method for evaluating the shear performance of shear nails in a steel-LUHPC composite structure, characterized in that: The following steps are involved: 1) Establish the calculation formula of shear bearing capacity of shear studs in steel-LUHPC composite structure: In the formula, A std is the cross-sectional area of the shear stud; f cu 、f std is the compressive strength of the concrete cube and the tensile strength of the shear nail; E c 、E s is the elastic modulus of concrete and shear studs; a, b, c are all constants; 2) The load-slip curve of shear studs in steel-LUHPC composite structures is proposed: Where, P is the shear force value of a single shear nail; P u is the shear bearing capacity of a single shear stud; s is the relativized slip.
2. The method for evaluating the shear performance of shear studs in a steel-LUHPC composite structure according to claim 1, characterized in that: In the step 1), regression fitting is performed on the three parameters a, b, and c, and a=0.003, b=0.33, and c=0.17 are obtained; The calculation formula for the shear bearing capacity of the shear studs in the steel-LUHPC composite structure is:
3. The method for evaluating the shear performance of shear nails in a steel-LUHPC composite structure according to claim 1, characterized in that: In the step 2), the push-out test results are fitted to obtain x=1.96, y=1.57, at which time the correlation coefficient R=0.951; Then the load-slip curve of the shear studs in the steel-LUHPC composite structure is: